Complete genome sequence of Bradyrhizobium sp. strain C-145, a nitrogen-fixing rhizobacterium used as a peanut inoculant in Argentina - Nievas, Fiorela Lujan (2022)
We present the complete genome sequence of Bradyrhizobium sp. strain C-145, one of the most widely used nitrogen-fixing rhizobacteria for inoculating peanut crops in Argentina. The genome consists of 9.53 Mbp in a single circular chromosome and was determined using a hybrid long- and short-read assembly approach.